PENINGKATAN KETERAMPILAN DESAIN GRAFIS PADA SISWA MULTIMEDIA SMK IBRAHIMY 1 SUKOREJO - Putri Anindya Damayanti; Fitri Elvi Karisma; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
In The Current millenial and digital design has become a demand in the creative industry today. In this case, vocational high school student majoring in Multimedia or Visual Communication Design need more graphic design skill. This training was held at Ibrahimy 1 Vocational High School, Sukorejo which is still under the auspices of the Salafiyah Syafiiyah Sukorejo Islamic Boarding School, specifically student majoring in Multimedia. The puspose of this community services is to strengthen the abilities and skills of vacationnal high school students using various CorelDraw graphic desain software as provisions is facing the work and enterpreneurship in the creative industry. The Method of implementing this community service avaible in the Coreldrwa application. The result of the training were that most students had an increased understand understandding of the basic concept desighn, design elements and principles of visual aesthetics and student were able to operate basic Coreldraw features such as creating and changing a object, adjusting color and using layers and simple effects. This had a positive impack impact on increasing students skill in designing logos, curicculum vitae and also a posters.